Determinants of tuberculosis: an example of high tuberculosis burden in the Saharia tribe - Gupta, Parul; Singh, Pushpendra; Das, Aparup; Kumar, Ravindra (Frontiers in Public Health, 2023)
Tuberculosis (TB) is a significant public health problem among the Saharia community, an underprivileged tribal group in the west-central part of India. There are several challenges for India’s TB control program to curtail TB in the Saharia tribe. Malnutrition, poor health sector facilities, lower socio-economic status, and substance abuse are interconnected and synergistic factors contributing to a high burden of TB in the Saharia tribe. In this review, efforts are made to collate the findings of previous studies discussing the causes of high burden of TB in the Saharia tribe, social gaps for mitigating these preventable risk factors of TB in the Saharia tribe, and the plausible solutions for closing these gaps. The concept of Health in All Policies and intersectoral co-ordination is needed for the reduction of TB in the Saharia tribe and to make India TB-free by the year 2025.